KELOMPOK TANI SEBAGAI BASIS KETAHANAN PANGAN FARMER GROUP AS BASIS OF FOOD STOCK - Hariadi, Sunarru Samsi (Jurnal Ilmu-Ilmu Pertanian, 2007)
Indonesia is agrarian country that most of farmers have small land acreage, so that is not efficient. In several areas often occurred famine. Some problems were faced by farmers can be solved by join together namely through farmer group. Farmer group can be used as basis of food stock. In every harvesting , members of farmer group give small part of their harvest to group for food stock, so each farmer group in village have function as basis food stock. Food stock can be larger through join several farmer groups in subdistricts level, regency level, reach province level.